2014
DOI: 10.1002/poc.3377
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of chlorination withtert-butyl hypochlorite (TBuOCl)

Abstract: The chlorination reactions of nitrogenous organic compounds (2,2,2-trifluoroethylamine, benzylamine, glycine, and dimethylamine) by tert-butyl hypochlorite ( t BuOCl) were studied at 25°C, ionic strength 0.5 M and under isolation conditions. The kinetic results obtained in the formation processes of the corresponding N-chloramines in acid medium (pH = 5-7) are summarized in this paper. Kinetic studies showed a first order with respect to t BuOCl concentration. The chlorination reactions involving benzylamine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…In the present work, the rate constants obtained for the reactions of OXA with HOCl and t BuOCl were similar and higher than the rate constants obtained in the reaction with NCS. These values follow the same trend as those found with other nitrogenous compounds HOCl0.25emtBuOCl0.25em>0.25emnormalNnormalCnormalS …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present work, the rate constants obtained for the reactions of OXA with HOCl and t BuOCl were similar and higher than the rate constants obtained in the reaction with NCS. These values follow the same trend as those found with other nitrogenous compounds HOCl0.25emtBuOCl0.25em>0.25emnormalNnormalCnormalS …”
Section: Discussionsupporting
confidence: 88%
“…According to the bibliographic information for the N ‐chlorination reactions using t BuOCl as a chlorinating agent, a reaction mechanism is proposed in which the two possible acid‐base equilibriums of the reactive species are included (Scheme ). On the other hand, taking into account the experimental conditions used in this work, the t BuOCl is going to be the chlorinating species.…”
Section: Mechanismmentioning
confidence: 99%
“…They found a chlorine transfer process in both cases, from NCS to a nitrogenous compound, generating the corresponding Nhalamines. Interestingly, when the same group 142 examined the effect of a chlorination reaction involving nitrogenous organic compounds using tert-butyl-hypochlorite ( t BuOCl), they selected 2,2,2-trifluoroethylamine, benzylamine, glycine, and dimethylamine to produce the corresponding homologous Nhalamines after chlorination treatment (see Figure 19C).…”
Section: Acyclic N-halaminesmentioning
confidence: 99%
“…To understand and discover new methods for synthesizing organic amine N -halamines, Pastoriza’s group , tried reacting organic amine with oxidative halogen-containing organic compounds rather than free chlorine and found that a reaction between nitrogenous organic compounds and one N -halamine can form alternative N -halamines. For example, using a transformation reaction involving N -chloro- N -methyl-p-toluenesulfonamide (NCNMPT) with nitrogenous organic compounds at 25 °C, they obtained corresponding amine N -halamine products, as seen in Figure A .…”
Section: Synthesis Of N-halaminesmentioning
confidence: 99%
“…tert -Butyl hypochlorite ( t BuOCl), commercially available and inexpensive, is a highly reactive chlorinating agent that could be kept stable in the cold for a few months. 14 In addition, t BuOCl also exhibits other attractive features, for instance, the release of t BuOH, which could be seen as an environmentally benign by-product. Furthermore, t BuOCl also has a higher chlorine atom economy compared with other chemicals commonly used for chlorination (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%